Study of sway swings on container trailer trucks - Razali, Mohd Faiz (2022)
In this writing, the study of the stability of containers carried by trailer is the main point. Various methods and specific conditions are studied to see the proportion of stability of this container to avoid unwanted accidents. Usually the swing problem that occurs in the container has many contributing factors either directly or indirectly. Among them are the position of the container, the weight of the container, the speed of the vehicle, truck and trailer design, vehicle suspension technology, vehicle tire technology, weather conditions, road conditions and more. This study will analyse some of these things from the experimental findings and the research study of the level of stability that occurs. Thus, the main purpose of this project is to study the oscillation rate that occurs on the container on the trailer and how to reduce the oscillation rate by taking into account several factors stich as installing sway bars, connector mounting plate effectiveness, container position analysis and laboratory experiments. Through several disciplines of the procedure, which is to set the experimental speed at 4 km/hr, 7 km/hr and 10 kmvhe in the front, middle and rear positions. with weights of 700 g, 1400 g, 2100 g and 2800 g. So it can be seen that the correct position of the container is among the most important factors that need to be taken into account for the study. It is also proportional to the speed of the vehicle carrying the container. For the study of mathematical analysis will also greatly help this experiment to obtain the accuracy of the study. In this study as well, also make improvements such as in -depth research through MATLAB and other aerodynamic measurement applications, but require larger study parameters. It is hoped that the results of this study can help to some extent on the statistics of trailer accidents in Malaysia.